On the Diophantine equations z2 = k(k2 + 3) and z2 = k(k2 + 12) (Journal of Bangladesh Academy of Sciences, 2021)
This paper provides an analytical method of finding all the (positive, integral) solutions of the Diophantine equation z2 = k(k2+3). We also prove analytically that the Diophantine equation z2 = k(k2+12) has no positive, integer solution.J. Bangladesh Acad. Sci. 45(1); 127-129: June 2021